Oocyte competence is maintained by m(6)A methyltransferase KIAA1429-mediated RNA metabolism during mouse follicular development - Hu, Yue (Cell Death Differ, 2020)
KIAA1429 (also known as vir-like m(6)A methyltransferase-associated protein (VIRMA)), a newly identified component of the RNA m(6)A methyltransferase complex, plays critical roles in guiding region-selective m(6)A deposition. However, in mammals, whether KIAA1429 mediates RNA m(6)A regulatory pathway functions in vivo remains unknown. Here, we show that the Kiaa1429-specific deficiency in oocytes resulted in female infertility with defective follicular development and fully grown germinal vesicle (GV) oocytes failing to undergo germinal vesicle breakdown (GVBD) and consequently losing the ability to resume meiosis. The oocyte growth is accompanied by the accumulation of abundant RNAs and posttranscriptional regulation. We found that the loss of Kiaa1429 could also lead to abnormal RNA metabolism in GV oocytes. RNA-seq profiling revealed that Kiaa1429 deletion altered the expression pattern of the oocyte-derived factors essential for follicular development. In addition, our data show that the conditional depletion of Kiaa1429 decreased the m(6)A levels in oocytes and mainly affected the alternative splicing of genes associated with oogenesis. In summary, the m(6)A methyltransferase KIAA1429-mediated RNA metabolism plays critical roles in folliculogenesis and the maintenance of oocyte competence.